Subjective Perceptions of Occupational Fatigue in Community Pharmacists - Taylor L. Watterson; Michelle A. Chui (MDPI AG, 2023)
Introduction: Community retail pharmacists are experiencing unsafe levels of stress and excessive demands within the workplace. One aspect of workload stress that has been overlooked among pharmacists is occupational fatigue. Occupational fatigue is a characteristic of excessive workload including increased work demands and reduced capacity and resources to complete the work. The goal of this study is to describe the subjective perceptions of occupational fatigue in community pharmacists by using (Aim 1) a previously developed Pharmacist Fatigue Instrument and (Aim 2) semi-structured interviews. Methods: Wisconsin community pharmacists were eligible to participate in the study and recruited via a practice-based research network. Participants were asked to complete a demographic questionnaire, a Pharmacist Fatigue Instrument, and semi-structured interview. Survey data were analyzed using descriptive statistics. Interview transcripts were analyzed using qualitative deductive content analysis. Results: Totally, 39 pharmacists participated in the study. From the Pharmacist Fatigue Instrument, 50% of the participants stated they had times where they were not able to go above and beyond standard patient care on more than half of the days they worked. A total of 30% of the participants reported that they found it necessary to take short-cuts when providing patient care on more than half of the days they worked. Pharmacist interviews were separated into overarching themes including mental fatigue, physical fatigue, active fatigue, and passive fatigue. Conclusions: The findings highlighted the pharmacists' feelings of despair and mental fatigue, fatigue's connectedness to interpersonal relationships, and the complex nature of pharmacy work systems. Interventions aimed at improving occupational fatigue in community pharmacies should consider key themes of fatigue that pharmacists are experiencing.